1995
DOI: 10.1002/masy.19950950115
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization with metallocene catalysts. Hydrooligomerization and NMR investigations concerning the microstructure of poly(cyclopentenes)

Abstract: I -21: Hydrooligomerizations and polymerizations of cyclopentene were carried out using Cs, Cz and CpV symmetric zirconocenes and methylaluminoxane as catalyst. The structure of the hydrotrimers was investigated by one-and twodimensional NMR spectroscopy and correlated to the structure of the polymers. The assignments for the 13C-NMR spectrum of the cis-I ,3-enchained hydrotrimer made by Collins [3] are corrected. Cis-I ,3-enchainment of the configurational base units in the poly(cyc1opentenes) is confirmed. r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Cyclic groups on the monomer can be introduced into the polymer as cis-fused cycloalkane groups. [7][8][9][10][11] The polymerization of non-conjugated dienes can also be used to synthesize polymers with cycloalkane groups because chain growth is accompanied by monomer ring closure. 12 Early transition metal complexes have been extensively used in cyclopolymerization reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic groups on the monomer can be introduced into the polymer as cis-fused cycloalkane groups. [7][8][9][10][11] The polymerization of non-conjugated dienes can also be used to synthesize polymers with cycloalkane groups because chain growth is accompanied by monomer ring closure. 12 Early transition metal complexes have been extensively used in cyclopolymerization reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Metallocene catalysts are effective not only for polymerization of common olefins, such as ethylene and propylene, but for polymerization of cycloolefins. The copolymerization of ethylene1–22 or propylene23 and norbornene (NB) with a variety of metallocene catalysts was conducted, and the structure and properties of the copolymer are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…After 1,2-insertion of the monomer, b-hydrogen elimination and reinsertion resulted in 1,3-insertion.An achiral catalyst Cp 2 ZrCl 2 produces cisrich but atactic poly(cyclopentene) that is amorphous polymer [180,181].A few chiral zirconocenes such as rac-Me 2 Si(Ind) 2 ZrCl 2 (3, R 1 =R 2 =H) [181] and rac-C 2 H 4 (Ind) 2 ZrCl 2 (1b) [180] give highly cis-isotactic polymer, while rac-C 2 H 4 (THInd) 2 ZrCl 2 (2) gives cis-(60%) trans-mixed polymer [182,183]. The C s -symmetric complex Ph 2 C(Cp)(Flu)ZrCl 2 (11)/MAO showed low stereoselectivity [181]. 208 N. Suzuki Studies on hydrooligomerization of norbornene revealed that 3 predominantly gave the meso,meso-isomer (66-71%), and 11 gave the rac,rac-trimer in 55-78% selectivity (Fig.…”
Section: Polymerization Of Cycloolefinsmentioning
confidence: 99%